Employee Performance Assessment using Analytical Network Process and Rating Scale - Riska Septifani; Panji Deoranto; Tiyas Widya Armanda (Department Industrial Engineering, University of Muhammadiyah Malang, 2020)
Employee performance assessment is an essential aspect of a company. This study aims to assess employee performance based on Analytical Network Process (ANP) and rating scale. ANP was employed to determine the importance of the criteria. Meanwhile, the rating scale was used to analyze the results of the employee performance assessment. The results of the study showed the weights of the criteria. The highest to lowest weights in sequence included the skills to carry out tasks, job performance, ability to cooperate, employment relationship, and personality. Based on the assessment of fifty-three employees of HRD and Corporate Secretary and General Counsel Department, one employee showed outstanding performance, four employees exemplified high performance, forty-five employees met the standard performance, and three employees had low performance.